Cultivating Shared and Contextual Learning and Teaching: Reflections on an Immersive and Collaborative Approach to Journeying with Students in Los Angeles - Glenn, Mary (Christian education journal, 2025)
In the wake of the global pandemic, polarization, displacement, and increased social isolation, people are seeking shared, practical, accessible, and integrated learning. A methodology of collaborative teaching and communal learning in place helps students to find connection (to each other, God, and place), cultivate hope, and partner with God's presence in the city. This article provides insights from shared learning, collaborative teaching, and journeying in Los Angeles through an urban immersion course we have co-taught since 2010.